2010
DOI: 10.1159/000280102
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Effects of Early Maternal Separation and Variable Chronic Stress on Vasopressinergic Activity and Glucocorticoid Receptor Expression in Adult Rats

Abstract: The aim of the present study was to investigate the influence of early maternal separation on Fos, arginine vasopressin (AVP) and glucocorticoid receptor (GR) expression in the medial parvocellular portion of the paraventricular hypothalamic nucleus (PaMP), and GR expression in the hippocampus of adult male and female rats subjected to variable chronic stress (VCS). Male and female Wistar rats were isolated 4.5 h daily, during the first 3 weeks of life. At 48 days of age, the rats were exposed to VCS. Nonmater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…In these animals, lower levels of ACTH and plasmatic corticosterone were detected compared with NMS-CVS (Renard et al, 2007). They also showed a greater number of GR immunoreactive cells in CA areas compared to controls (Renard et al, 2010).…”
Section: J U S T a C C E P T E Dmentioning
confidence: 73%
“…In these animals, lower levels of ACTH and plasmatic corticosterone were detected compared with NMS-CVS (Renard et al, 2007). They also showed a greater number of GR immunoreactive cells in CA areas compared to controls (Renard et al, 2010).…”
Section: J U S T a C C E P T E Dmentioning
confidence: 73%
“…While MS seems to result in significantly higher corticosterone stress responses in adulthood (Ladd et al, 2004, 2005; Plotsky et al, 2005; Lippmann et al, 2007; Lajud et al, 2012), the additional experience of chronic stress in adult life has been shown to normalize these responses to the level observed in non-stressed non-MS controls (Ladd et al, 2005) or to even reduce basal ACTH and corticosterone levels compared to stressed non-MS animals (Renard et al, 2007). These effects were associated with an upregulation in hippocampal GR expression, and a normalization of GR levels in the PVN (Renard et al, 2010). Moreover, exposure to chronic stress reduced amygdala CRH mRNA expression in MS offspring and did not induce an increase in PVN expression levels (as observed in the stressed control animals; Ladd et al, 2005).…”
Section: Early Life Stress Effects In a “Matching” Stressful Adult Enmentioning
confidence: 99%
“…Many studies have indicated pronounced sex-dependent differences of MS-induced effects (Barna et al 2003;Oreland et al 2009;Renard et al 2010;Rosztoczy et al 2003). This is of particular relevance to IBS where significantly more GI, psychological and somatic symptoms are associated with the female gender (Cain et al 2009).…”
Section: Maternal Separationmentioning
confidence: 99%